Is earning detrimental to learning? Experiences of medical students from traditional and low socioeconomic backgrounds. Issue 1 (1st December 2022) - Anane, Melissa; Curtis, Sally
Abstract : Background: Medical schools are striving to produce a representative workforce through admissions processes that actively encourage applications from students with backgrounds of social and financial disadvantage. Such medical students frequently have reduced financial support and need to undertake paid employment while studying. However, there is limited evidence to show how a lack of financial support and undertaking paid employment impacts those studying for medical degrees, who are not from affluent backgrounds. Method: A mixed methods approach was used for this single site, exploratory study. A questionnaire on paid employment was distributed to undergraduate medical students. Those respondents in employment were invited to attend an interview to further explore their experiences. Interviews were recorded, transcribed, and analysed using inductive thematic analysis. Results: Questionnaire responses from 199 medical students were received and 11 semi-structured interviews conducted. Most students undertook paid employment during medical school and stated it had some benefits. However, the negative impact of paid employment was greater for LSE students: those who met the medical school's widening participation criteria. LSE students reported work was a necessity rather than a choice. They also had additional stress of financial responsibility for others, including parents or partners. Discussion: Compared to traditional medical students, LSE students report increased negative experiences from undertaking paid employment, with greater financial responsibility for themselves and others during their studies. Medical schools have a responsibility to adapt and provide appropriate support for all students. It is vital to understand and acknowledge the additional challenges students from LSE backgrounds face.